Crystal structure of acrinidinium tetrafluorohydrogenphthalate, C21H11F4NO4 - Liu Xin-Fang; Song Jun-Ya; Zhao Bei-Bei; Huang Shi-Jie (Zeitschrift für Kristallographie - New Crystal Structures)
C21H11F4NO4, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 9.5000(4) Å, b = 13.9989(7) Å, c = 14.1423(5) Å, α = 91.355(4)°, β = 108.542(4)°, γ = 98.958(4)°, V = 1756.02(14) Å3, Z = 4, R gt(F) = 0.0494, wR ref(F 2) = 0.1157, T = 293(2) K.